تقييم دور مستشاري الزبائن في تحقيق الاهداف الاتصالية للمؤسسة دراسة حالة مؤسسة جيزي - سناء, حفصي; عبلة, رزيق (جامعة الوادي - University of Eloued, 2023)
وفي خلاصتنا لهذين الفصلين ففي الفصل الأول تطرقنا إلى ماهية مؤسسة جيزي من لمحتها التاريخية ونشأتها وتطوراتها عبر السنوات وتبعا للهيكل التنظيمي لها وأهدافها نحو الاتصال، و المزيج التسويقي لها (منتج،تسعير،توزيع،ترويج)، وتوجهنا في الفصل الثاني إلى عرض الاستبيان وتحليله موجه لزبائن مؤسسة جيزي الذي عددَّنا له محاور تكمن في الاهداف الاتصالية وتحقيقها في التقييم والتفاعل الذي يقوم به مستشاري الزبائن تجاه الزبائن ومن بين هذه المحاور محور الاستقبال الذي يحظى بعبارته من الدرجة الأولى وهي موظف الاستقبال يجيب على استفسارات الزبون حول الشركة والخدمات والمنتجات التي تقدمها، ومحور التعرف بالمنتجات والاشهار لها الذي يحظى بعبارته من الدرجة الأولى وهي سعر البطاقة يتناسب مع خدمات المؤسسة، ومحور معالجة المشاكل الذي يحظى بعبارته من الدرجة الأولى وهي هل يستجيب الموظف للمشاكل المطروحة وبالطبع الموظف يجيب الزبون على كل مشكل يعيقه او يواجهه، والمحور الأخير توجيه الزبون الذي يحظى بعبارته من الدرجة الأولى وهي راضي باستمرار بخدمة جيزي. In our conclusion to these two chapters, in the first chapter we touched on what the Geezy Corporation is from its historical overview, its origins, and its developments over the years, according to its organizational structure, its objectives towards communication, and its marketing mix (product, pricing, distribution, promotion), and we headed in the second chapter to presenting and analyzing the questionnaire. For the customers of the Jeezy Foundation, for which we have enumerated axes that lie in the communication goals and their achievement in the evaluation and interaction that the customer advisors make towards the customers. With products and publicity for them, which has its phrase of the first degree, which is the price of the card commensurate with the services of the institution, and the axis of problem solving, which has its phrase of the first degree, which is whether the employee responds to the problems raised, and of course the employee answers the customer to every problem that hinders him or confronts him, and the last axis is directing the customer who has his phrase First class and consistently satisfied with Gezi's service.
Keywords: مستشاري الزبائن - الاهداف الاتصالية - المؤسسة - مؤسسة جيزي; Customer advisors - communication objectives - the institution - Jeezy Foundation